Early axonal damage and progressive myelin pathology define the kinetics of CNS histopathology in a mouse model of multiple sclerosis - Recks, Mascha S.; Stormanns, Eva R.; Bader, Jonas; Arnhold, Stefan; Addicks, Klaus; Kuerten, Stefanie (Clinical Immunology, 2013)
Studies of MS histopathology are largely dependent on suitable animal models. While light microscopic analysis gives an overview of tissue pathology, it falls short in evaluating detailed changes in nerve fiber morphology. The ultrastructural data presented here and obtained from studies of myelin oligodendrocyte glycoprotein (MOG):35-55-induced experimental autoimmune encephalomyelitis (EAE) in C57BL/6 mice delineate that axonal damage and myelin pathology follow different kinetics in the disease course. While myelin pathology accumulated with disease progression, axonal damage coincided with the initial clinical disease symptoms and remained stable over time. This pattern applied both to irreversible axolysis and early axonal pathology. Notably, these histopathological patterns were reflected by the normal-appearing white matter (NAWM), suggesting that the NAWM is also in an active neurodegenerative state. The data underline the need for neuroprotection in MS and suggest the MOG model as a highly valuable tool for the assessment of different therapeutic strategies. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Axonal pathology; EAE; Electron microscopy; MOG:35-55; MS; Neurodegeneration